2007
DOI: 10.1016/j.cct.2006.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Value of recruitment strategies used in a primary care practice-based trial

Abstract: This analysis provides suggestions for future recruitment efforts and research. Translational studies with limited funds could consider multi-modal recruitment approaches including in-person presentations to practice groups and exploitation of previous relationships, which require the providers to opt-out, and interactive opt-in approaches which rely on borrowed networks. These approaches can be supplemented with non-relationship-based opt-out strategies such as cold calls strategically targeted to underrepres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 27 publications
1
89
0
Order By: Relevance
“…For example, the 'physicians recruiting physicians' strategy leads to acceptable recruitment rates but may not include representative practices. 6 One example of a potentially effective approach to practice recruitment that is built on an intimate knowledge of research in primary care involves the use of research information sheets for practices. 7 These provide a template for the generation of clear and succinct information about a trial or research study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the 'physicians recruiting physicians' strategy leads to acceptable recruitment rates but may not include representative practices. 6 One example of a potentially effective approach to practice recruitment that is built on an intimate knowledge of research in primary care involves the use of research information sheets for practices. 7 These provide a template for the generation of clear and succinct information about a trial or research study.…”
Section: Resultsmentioning
confidence: 99%
“…An additional factor in the invitation method that may have led to a representative recruitment was the issuing of invitations to all practices in the two PCTs, rather than just those perceived to be interested in research or the topic of the trial. 6 • An interest in research was identified by participating GPs as an important reason for joining the trial, even though not all participating GPs had previous experience of research.…”
Section: Original Papers Original Papersmentioning
confidence: 99%
“…The greater success of RM3 appears to be attributable to who did the recruiting. Specifically, having a medical peer telephone a GP's surgery greatly simplified access to the practice, a finding that has been previously noted (Veitch et al 2001;Sellors et al 2002;Ellis et al 2007). Reasons why the medical-peer approach works is the ability to pass the practice 'gatekeeper', usually a receptionist, because of their respect and credibility (Heywood et al 1995) and the strength of their personal networks and relationships (Asch et al 2000).…”
Section: Discussionmentioning
confidence: 60%
“…Whenever possible, research activities should be executed by research staff, not by physicians and clinical staff [24,27]. Finally, physicians are more likely to participate if the study results will positively impact their clinical practices and enable the physicians to develop further their patient-care skills [24,30]. Researchers should consider ways to provide individualized feedback to physicians based on the results of the study [24] or link the project to the physicians' own professional development [26].…”
Section: Recruiting Health-care Professionalsmentioning
confidence: 98%